A Survey of social interaction among diverse students in Malaysian higher learning institutions - Ramlee Mustafa,; Norzaini Azman,; Faridah Karim,; Abdul Razak Ahmad,; Maimun Aqsha Lubis, (Universiti Kebangsaan Malaysia, 2009)
Polarisation among diverse ethnic groups in higher learning institutions is becoming a delicate matter in many multiracial societies. Higher education institutions are expected to be the beacon for harmony by bridging racial differences, given the atmosphere of reason, inquiry and collegiality. Higher Education institutions are in unique position to address diversity issues by creating environment that will allow positive interaction among students from different ethnicities and backgrounds. Thus, the purpose of this article was to report results of an empirical study on ethnic relation as perceived by first and final year undergraduates. The Campus Social Environment Survey was designed to gauge various aspects of cross racial interaction among the undergraduates in selected private and public institutions of higher learning in Malaysia. The initial analysis focuses on descriptive data on four main constructs of racial integration — accommodation, acculturation, assimilation and amalgamation. Implications and recommendations for teaching and learning as well as for future research are presented and discussed.